다문화 청소년의 문화적응 스트레스와 정신건강의 관계 -사회적 지지 매개 효과 중심으로 - 장선아(Seon-Ah Jang); 고정훈(Jeonghun Go) (한국콘텐츠학회 논문지, 21(1), 2021)
This study is to investigate the mediating effects of social support on the relationship between acculturative stress and mental health of multicultural youth. The results of the study were as follows: 1.573 of the 4th(middle 1) to 6th(middle 3) of the multicultural youth panel were analyzed by AMOS 22.0. First, the acculturation stress of multicultural youths had a positive effect on mental health. Second, acculturation stress of multicultural youths had a negative effect on social support. Third, social support of multicultural youths had a negative effect on mental health. Fourth, social support of multicultural youths had a mediating effect on the effect of acculturation stress on mental health. This result shows that the stress of multicultural youths in the process of adapting to the dual culture negatively affects social support, and this social support has a positive effect on the mental health of multicultural youths. 본 연구는 다문화 청소년의 문화적응 스트레스가 정신건강에 미치는 영향에서 사회적 지지의 매개 효과 규명을 목적으로 한다. 연구방법은 다문화 청소년 패널 제4차(중1)~제6차(중3)의 1,573명을 AMOS 22.0으로 분석한 결과는 다음과 같다. 첫째, 다문화 청소년의 문화적응 스트레스는 정신건강에 정적인 영향을 미치는 것으로 나타났다. 둘째, 다문화 청소년의 문화적응 스트레스는 사회적 지지에 부적인 영향을 미치는 것으로 나타났다. 셋째, 다문화 청소년의 사회적 지지는 정신건강에 부적인 영향을 미치는 것으로 나타났다. 넷째 다문화 청소년의 사회적 지지는 문화적응 스트레스가 정신건강에 미치는 영향에서 매개영향을 미치는 것으로 나타났다. 이는 다문화 청소년이 이중문화에 적응하는 과정에서 겪는 스트레스로 인하여 사회적 지지에 부적인 영향을 미치고, 이런 사회적 지지는 다문화 청소년의 정신건강에 정적인 영향을 미치는 것을 밝혔다.